Developing a training course to teach research skills to people with learning disabilities: "It gives us a voice. We CAN be researchers!". (22nd May 2020) - Tuffrey‐Wijne, Irene; Lam, Claire Kar Kei; Marsden, Daniel; Conway, Bernie; Harris, Claire; Jeffrey, David; Jordan, Leon; Keagan‐Bull, Richard; McDermott, Michelle; Newton, Dan; Stapelberg, Diane
Accessible Summary: We are eight people with learning disabilities. We did a training course at a university in London. It was called "Learning how to do research." We learned about the 10 steps in research, and we practised how to do research. Part of the course was doing our own research project. Then, we presented it to an audience. In this article, our tutors describe the course. We say what it was like for us. Most of us were nervous about doing the course, but we learnt a lot from it. There are not many opportunities for people with learning disabilities to learn about research. We think more people with learning disabilities should have the chance to do it. We hope this article helps other teachers to start a research course. We can be researchers! Being involved in research gives us a voice. Abstract: Background: Within learning disability research, it is important to involve people with learning disabilities at all stages, but there are limited opportunities for them to learn about the research process or to gain research skills. Method: An eight‐session research training course for people with learning disabilities was developed and piloted at a university in London. The focus was on understanding the research process and gaining practical skills in collecting, analysing and presenting research data. Training methods were experimental, with an emphasis on learning by experience in a "fun" way. Results: Ten people with learning disabilities completed the course, showing great enthusiasm and commitment. During the final sessions, students developed and conducted their own research projects, choosing "Employment" as their research topic. The training methods were well received. Benefits included an increase in confidence and new work opportunities for several of the students. This paper was co‐authored by the tutors and most of the course graduates. Conclusion: It is possible for people with learning disabilities to become skilled researchers, but in order to do so, it is important that they have adequate training opportunities. Funding should be made available for more such courses.